Diamond light source electron beam position feedback: Design, realization and performance - Heron, MT; Abbott, MG; Dobbing, JA; Rehm, G; Rowland, J; Uzun, IS; Duncan, SR (Joint Accelerator Conferences, 2009)
The electron beam in the Diamond Synchrotron Light Source is stabilised in two planes using the Fast Orbit Feedback system. This feedback system takes the beam position from 168 Libera electron beam position monitors for each plane, and calculates offsets to 336 corrector power supplies at a sample rate of ~10 kHz. The design and realization of this system, together with its performance and operational experience will be presented.